THE COMPLEXITY OF FUNCTIONAL SYNTACTIC STRUCTURES OF SARCASM EXPRESSIONS - Nurul Hasana; Agus Subiyanto (Leksema: Jurnal Bahasa dan Sastra, 2024)
This linguistic research adopted a descriptive qualitative approach that focuses on the syntactic structure of sarcasm expressions. The data for this study were collected from the popular television series Friends, which focused on the character Chandler Bing. Bing was one of the most known characters among various sitcom series with iconic sarcasm. This study aimed to identify the complexity of the syntactic functional structures including adjuncts, specifiers, and complements. Employing the x-bar theory for analysis, the study categorized the collected data into complex adjuncts, complex specifiers, and complex complements, accompanied by their respective x-bar schemas and thorough explanations. The results showed that Bing's sarcastic expressions exhibit complexity across a variety of functional structures with the various word categories as the construction. The most common complex form was identified in the complement structure. This study contributed to a nuanced understanding of syntactic aspects of sarcasm, especially within the linguistic framework of his x-bar theory.